On Institutional Environment and Leverage of Small and Medium‐Sized Enterprises - G Savvakis; Kenourgios, D.; Th. Papageorgiou
We analyze the impact of the institutional environment on the leverage of European listed SMEs for the period 2005-2018. We use a broad range of institutional quality, judicial efficiency and corruption measures, along with several firm-specific and macro control variables, to identify different transmission channels on leverage. By performing a panel data analysis into the fixed effects filter estimator framework, along with several model specifications and robustness tests, the results show that better institutions, stronger judicial effectiveness and higher corruption decrease leverage. In terms of active transmission channels, increased investment under regimes of better institutional quality tends to increase leverage. Higher judicial efficiency accompanied by increased profitability tends to decrease, while higher institutional quality accompanied by higher investments tends to increase leverage, bringing more bank credit. Increasing profitability under regimes of decreased corruption decreases leverage. This last finding is even more pronounced for medium enterprises, as opposed to micro enterprises. The most significant factors associated with leverage are profitability, asset structure, cost of borrowing, stock market development and size, while an age effect is rejected. Pecking order theory seems to better fit the European SMEs capital structure choices under several institutional states.